Vocational students’ HOTS and HOTSEP overview in developing ITA learning model - Ana Amalia Islami; Henita Rahmayanti; Tuti Iriani; Ilmi Zajuli Ichsan; Isil Koc; Rahmawati Darussyamsu (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
Practical learning activities carried out in remote situations during the COVID-19 pandemic triggered vocational students to take advantage of the surrounding environment as a learning resource. The process also determines how their HOTS and HOTSEP are. A learning model that can accommodate the skills is needed, such as ITA (Identify problems–Think and write–Analysis and argumentation) model. This learning model utilizes environmental issues intending to guide students to understand the environment through an online platform. This study aimed to analyze the HOTS and HOTSEP of vocational students, as the basis for developing a new learning model. The research sample consisted of 61 students with 29 male students and 32 female students. The sample was selected by simple random sampling. Data were analyzed using descriptive analysis. The results showed that the total scores of students' HOTS (17.14) and HOTSEP (18.74) were suggested as very low categories. Thus, the students' skills need to improve actively with innovative learning models, such as the application of the ITA model.